Traditional Gender Attitudes towards the Role of Husbands in Domestic Violence towards Women: A Qualitative Analysis - Masarah Mohamad Yusof, Mohd Haizzan Yahaya, Suzanna Awang Bono, Farhana Kamarul Bahrin (International Journal of Advanced Science and Technology, 2020)
Husbands' unwavering attitude has caused women to bear the burden of responsibility and cause both physical and emotional stress. It is thus important to be acquainted with the impact of the husbands’ inability in managing family roles conflict especially on gender role conflict among wives. A qualitative study was conducted to identify factors in the husbands’ inability in managing domestic responsibilities that led to the formation of gender role conflict over female victimization and to trigger domestic violence. A total of 15 domestic violence victims in Penang, Malaysia were recruited through purposive sampling and snowball techniques for an in-depth interview. The results of the study suggested that there are three forms of the inability of husbands’ in taking responsibility of their role in a family that triggered the formation of gender role conflict through the burden of wife responsibilities in the context of domestic violence. These include the husband's inability in managing their own self-esteem, financial problems, and responsibility towards children. The findings from the current study propose that family institutions need to undergo individual and small group social work interventions made up of family members. Some techniques in family therapy are best used to help couples resolve existing role conflicts. At the same time, it enhances the social functioning of spouses in addressing domestic violence and to strengthen the family institution.Keywords: female victimization, domestic violence, husband's management inability, gender role conflict